Storax Inhibits Caveolae-Mediated Transcytosis at Blood-Brain Barrier After Ischemic Stroke in Rats - Zhou, Min; Li, Dongna; Shen, Qian; Gao, Lei; Zhuang, Pengwei; Zhang, Yanjun; Guo, Hong (Frontiers in Pharmacology, 2022)
Background and Purpose: Blood-brain barrier (BBB) disruption following ischemic stroke (IS) contributes to hemorrhagic transformation, brain edema, increased neural dysfunction, secondary injury, and mortality. The prevailing view attributes the destruction of tight junction proteins (TJs) to the resulting BBB damage following IS. However, recent studies define a stepwise impairment of the transcellular barrier followed by the paracellular barrier which accounts for the BBB leakage in IS. The increased endothelial transcytosis that has been proven to be caveolae-mediated, precedes and is independent of TJs disintegration. Emerging experimental investigations suggested Storax have the effect on cerebral ischemia injury and blood brain barrier damage. This study aimed to test our hypothesis that Storax inhibits caveolae-mediated transcytosis at blood-brain barrier after ischemic stroke in rats. Methods: In this study, male Wistar rats (250-300g) were subjected to transient middle cerebral artery occlusion (t-MCAO). Brain water content and the cerebral infarction assessed by the brain tissue drying wet method and TTC assay. The BBB permeability was detected by the leakage of Evans blue and Albumin-Alexa594. Ultrastructure of BBB was examined by transmission electron microscopy (TEM). Cav-1, Mfsd2a, AQP4, PDGFR-β, ZO-1 and Occludin was quantified by western blot and immunofluorescence. Results: The permeability of BBB increased at 6 h after IS in rats, and treatment with storax can significantly inhibited the transcytosis of Albumin-Alexa594. TEM results showed that the number of caveolae and the pericyte coverage were increased. Similarly, western blot assay showed that storax can increase the expression of Mfsd2a and PDGFR-β, and decrease the expression of Cav-1 and AQP4. However, the expression of TJs related proteins ZO-1 and Occludin have no significant change. In addition, immunofluorescence assay showed that storax can upregulate the expression of Mfsd2a and downregulate the expression. Conclusions: Storax can inhibit the permeability of BBB at the early stage after IS, and its potential mechanism may via inhibiting caveolae-mediated transcytosis.